2002
DOI: 10.1016/s0169-4332(02)00068-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of asphaltenes from toluene on typical soils of Lublin region

Abstract: Adsorption of asphaltenes on soils is one of the important problems, though largely underestimated, in environment protection of Lublin region. Asphaltene adsorption properties affect the way the contamination spreads in soil. Analysis of this phenomenon may help in localisation and elimination of oil spills. The asphaltenes studied were obtained from local drills (Ś widnik near Lublin, Poland). In our previous paper, we investigated adsorption of asphaltenes from toluene on rock components (quartz, dolomite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…Langmuir-type isotherms indicating that asphaltene molecules form monolayer coverage on the solid surface were observed in most solid surfaces [5,[24][25][26]. Multilayer adsorption isotherms have been reported as well [4,24,[27][28][29]. Multilayer behavior was attributed to the aggregate formation and precipitation of asphaltenes in the bulk due to asphaltene association and further formation of hemimicelles.…”
Section: Introductionmentioning
confidence: 89%
“…Langmuir-type isotherms indicating that asphaltene molecules form monolayer coverage on the solid surface were observed in most solid surfaces [5,[24][25][26]. Multilayer adsorption isotherms have been reported as well [4,24,[27][28][29]. Multilayer behavior was attributed to the aggregate formation and precipitation of asphaltenes in the bulk due to asphaltene association and further formation of hemimicelles.…”
Section: Introductionmentioning
confidence: 89%
“…Asphaltenes adsorb at solid surfaces [1], essentially to produce monolayers of nanoaggregates, the latter comprising stacks of 6 asphaltene molecules, according to the Yen-Mullins aggregation model [26]; further aggregation of nanoaggregates to form clusters at sufficiently high concentrations leads to thicker adsorbed layers [27,28]. According to Adams' comprehensive review on asphaltene adsorption, by assuming 3 nm asphaltene (nano)aggregates with a density of 1200 kg/m 3 , the maximum surface coverage for an asphaltene monolayer is calculated to be 3.6 mg/m 2 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies on asphaltene adsorption on solid surfaces have been reported in the literature (Adams, 2014;González and Moreira, 1991;Marczewski and Szymula, 2002;Marlow, Sresty, Hughes, & Mahajan, 1987;Pernyeszi and Dékány, 2001;Pernyeszi, Patzko, Berkesi, & Dékány, 1998Szymula and Marczewski, 2002) to understand the influence of the asphaltene chemical structure and composition (Dudášová, Flåten, Sjöblom, & Øye, 2009;Dudášová, Simon, Hemmingsen, & Sjöblom, 2008), the solvent or precipitant used (Dubey and Waxman, 1991;Nassar, 2010), the surface chemistry (Dudášová et al, 2009;Franco, Montoya, Nassar, Pereira-Almao, & Cortés, 2013b. Nassar, 2010Nassar, Hassan, & Pereira-Almao, 2011a.…”
Section: Introductionmentioning
confidence: 99%